The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1186/s13044-016-0033-y
|View full text |Cite
|
Sign up to set email alerts
|

Predicting malignancy in thyroid nodules: feasibility of a predictive model integrating clinical, biochemical, and ultrasound characteristics

Abstract: BackgroundAlthough the majority of thyroid nodules are benign the process of excluding malignancy is challenging and sometimes involves unnecessary surgical procedures. We explored the development of a predictive model for malignancy in thyroid nodules by integrating a combination of simple demographic, biochemical, and ultrasound characteristics.MethodsRetrospective case-record review.We reviewed records of patients with thyroid nodules referred to our institution from 2004 to 2011 (n = 536; female 84 %, mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 31 publications
4
18
2
Order By: Relevance
“…Moreover, Li et al reported that the incidence of thyroid cancer in male patients was significantly higher than in female patients (p=0.003) [13]. In contrast to our results, studies conducted by El-Gammal et al and Witczak et al reported a high incidence of malignancy more in females than males [8,11]. However, a study by Jaheen et al found that the difference in the incidence of malignancy between men and women is not statistically significant [14].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Moreover, Li et al reported that the incidence of thyroid cancer in male patients was significantly higher than in female patients (p=0.003) [13]. In contrast to our results, studies conducted by El-Gammal et al and Witczak et al reported a high incidence of malignancy more in females than males [8,11]. However, a study by Jaheen et al found that the difference in the incidence of malignancy between men and women is not statistically significant [14].…”
Section: Discussioncontrasting
confidence: 99%
“…Instead, they reported that thyroid cancer is common among people aged 45 years and below [10]. Witczak et al reported that the age difference between patients with malignant diseases and those with benign diseases is not significant [11].…”
Section: Discussionmentioning
confidence: 99%
“…The median age was 41 years and 40 years, respectively. Witczac et al (2016), reported similar results which is in accordance with our study 18 . Recent studies reported that most thyroid malignancies occur in the middle age group 20-60y 17,18 .…”
Section: Outsupporting
confidence: 93%
“…On the other hand, Paul et al (2017) reported that incidence of malignancy is higher in females 16 . Other studies reported that there is no significant difference between both sexes regarding the incidence of malignancy 18,20,21 . However, after combining age to sex the significance was lost suggesting that sex is not a strong independent predictor of malignancy.…”
Section: Outmentioning
confidence: 89%
“…While several studies have attempted to identify biomarkers that are predictive of the likelihood of malignancy in patients with thyroid nodules in the general population, the data correlating these factors in radiation-induced thyroid cancer remain scarce. Several publications have shown that the risk of malignancy in sporadic thyroid nodules increases with serum thyrotropin (TSH) concentrations, even within the normal range (Boelaert et al 2006, Haymart et al 2008, Witczak et al 2016. In contrast, in a case-control analysis matching thyroid cancer cases with controls nested in the European Prospective Investigation into Cancer and Nutrition cohort (EPIC) study, Rinaldi and coworkers found that thyroid cancer risk was negatively associated with the TSH levels (Rinaldi et al 2014).…”
Section: Introductionmentioning
confidence: 99%